Pemenuhan Hak Narapidana Laki-Laki di Lembaga Pemasyarakatan Banda Aceh - Mahfud Mahfud; Rizanizarli Rizanizarli; Mukhlis Mukhlis; Tarmizi Tarmizi; Ainal Hadi (Universitas Syiah Kuala, 2014)
This article aims to explore the fulfilment of males’ prisoner rights at the Correctional Service Centre Banda Aceh. The indicators used to measure it are registration process, accommodation, sanitary facilities, clothes and beds, sport, health service, abuse by the guards, interaction with outside, worship facilities, case information, complain of prisoners, workshop, education and prisoners’ separation. The research reveals that the availability of clothes and beds, health service, education and prisoners’ separation at the centre are not maximally provided yet at the centre. The Fulfilment of Males’ Prisoner Rights at the Banda Aceh Correctional Service Centre